Evaluating the Possibility of Transfusion Medicine, Through Crossmatching in Juvenile Galapagos Sea Lions (Zalophus wollebaeki) - Gregory, Taylor M.; Parker, Maryanna; Deresienski, Diane; Alarcón-Ruales, Daniela; Muñoz-Pérez, Juan Pablo; Torres, Jorge; Gavilanes, Gabriela I.; Lewbart, Gregory A.; Páez-Rosas, Diego (Frontiers in Veterinary Science, 2022)
The Galapagos sea lion (Zalophus wollebaeki) is an endemic pinniped to the Galapagos archipelago, and like most wild mammals, is at risk for anemia due to trauma, infectious disease, and poor nutrition. This study evaluated the health status of 26 juvenile Galapagos sea lions on the island of San Cristobal prior to evaluating 100 crossmatch combinations. On evaluation, all but one sea lion had no major systemic abnormalities. Of the 100 crossmatches performed, 23% had minor reactions. The most significant reaction was weak macroscopic agglutination found in 4% of samples. The small percentage of agglutination reactions suggests a small proportion of naturally occurring alloantibodies in this species and may be consistent with a low risk of acute immune-mediated hemolytic transfusion reaction.